The inventory of oral stressed vowels in the Portuguese dialect of Graciosa, Azores - Polasek,Metodej (2012)
Each of the nine Azorean islands represents a specific speech community with a certain linguistic behavior which may or may not be analogous to the linguistic behaviors of other Azorean speech communities. The phonetic realization of stressed vowels constitutes its most important expression: there are more or less systematic changes of the vocalic timbres in relation to their standard Portuguese counterparts. This paper will describe acoustic properties of the stressed oral vowels in one particular Azorean speech community, the one of Graciosa Island, as well as the phonological processes which led to the shifts of the vocalic timbres of the stressed vowels in this particular dialect. It is a first step towards the main goal of the author: to develop a typology of the dialects, corresponding to individual islands, based on empirical acoustic data. One of the main issues is to find the most convenient method and instrumental tools for the study of particular dialects based on acoustic data.